REVEALING THE CONNOTATIVE MEANING OF THE FIGURATIVE LANGUAGE IN JAMES ARTHUR’S SELECTED SONG LYRICS - Hamza Jafar (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This article under the title “Revealing the Connotative Meaning of the Figurative Language in James Arthur’s Selected Song Lyrics” aims at revealing the connotative meaning of figurative language used in the Arthur’s song lyrics. Figurative Language is a language that uses words, sentences, or phrases with their meaning different from literal interpretations. The data are taken from several selected song lyrics by James Arthur in genius.com in the transcript form. To collect the data, the method used in this article is the documentation method. The collected data were analyzed by the qualitative method using the theory of figurative language proposed by Knickerbocker and Reninger (1963) to identify the types of figurative language and theory of connotative meaning proposed by Leech (1981) to reveal or interpret the intended meaning of figurative language.